1990
DOI: 10.1002/dvg.1020110523
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and genetic analysis of an antigenic determinant found on N‐linked oligosaccharides in Dictyostelium

Abstract: Dictyostelium discoideum synthesizes many highly immunogenic carbohydrates of unknown structure and function. We have used monoclonal antibodies prepared against one of these called CA1 to investigate its structure and the consequences of its loss. CA1 is preferentially expressed on lysosomal enzymes as a specific arrangement of mannose-6-SO4 residues on N-linked oligosaccharides. Mutant strains HL241 and HL243 do not express CA1, and synthesize a truncated lipid-linked oligosaccharide (LLO) precursor that lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…However, morphological descriptions of the membrane merger process occurring during endosome fusion are extremely rare. Study of cryo-immobilized and freeze-substituted D. discoideum cells at the EM level revealed that the membranes of some vacuoles were in tight contact and fusion events carbohydrate epitope present on D. discoideum lysosomal enzymes such as ␣-mannosidase and ␤-glucosidase (Knecht et al, 1984;Freeze et al, 1990), labeled small vesicular structures, that formed "rings of dots" around bigger, unlabeled vacuoles (marked by asterisks and also shown in higher magnification). Bar, 10 m. (C and D) Ultrastructure of late endosomes in wild-type D. discoideum cells that ingested BSA-Au particles for 60 min.…”
Section: Endosome-endosome Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, morphological descriptions of the membrane merger process occurring during endosome fusion are extremely rare. Study of cryo-immobilized and freeze-substituted D. discoideum cells at the EM level revealed that the membranes of some vacuoles were in tight contact and fusion events carbohydrate epitope present on D. discoideum lysosomal enzymes such as ␣-mannosidase and ␤-glucosidase (Knecht et al, 1984;Freeze et al, 1990), labeled small vesicular structures, that formed "rings of dots" around bigger, unlabeled vacuoles (marked by asterisks and also shown in higher magnification). Bar, 10 m. (C and D) Ultrastructure of late endosomes in wild-type D. discoideum cells that ingested BSA-Au particles for 60 min.…”
Section: Endosome-endosome Fusionmentioning
confidence: 99%
“…The following primary antibodies were used in this study: 1) a monoclonal antibody (mAb) 176-3-6 against coronin, an actin-binding protein (de Hostos et al, 1993) (gift from Dr. G. Gerisch, MPI for Biochemistry, Munich, Germany); 2) a mAb 221-342-5 (Neuhaus et al, 1998) against a common mannose-6-sulfate-containing carbohydrate epitope present on D. discoideum lysosomal enzymes such as ␣-mannosidase and ␤-glucosidase (Knecht et al, 1984;Freeze et al, 1990); 3) a mAb against horseradish peroxidase (HRP) from Vector Laboratories (Burlingame, CA); 4) a polyclonal antibody against cathepsin D (gift from Dr. J. Garin; CEA, Grenoble, France); 5) a mAb 221-1-1 against vacuolin (Jenne et al, 1998) (gift from Dr. M. Maniak, Abt. Zellbiologie, Universität GhK, Kassel, Germany); and 6) a mAb against a plasma membrane marker PM4C4 (mAb V4C4F3; Schwarz et al, 2000) (gift from Dr. J. Garin; CEA).…”
Section: Antibodiesmentioning
confidence: 99%
“…The vacuolar-H+-ATPase ( ) is associated with membranes of the contractile vacuole complex and, to a much lesser extent with endosomes (monoclonal antibody 221-35-2 against the A-subunit of the vacuolar-H+-ATPase (Neuhaus et al 1998)). The common Antigen-1 ( • ) is a M-6-P-containing epitope shared by D. discoideum lysosomal enzymes such as (-mannosidase and (-glucosidase (Freeze et al 1990) (monoclonal antibody 221-342-5 (Neuhaus et al 1998)). Dynamin A (_) is a GTPase potentially involved in vesicle scission and is localised around post-lysosomal vacuoles in a punctate fashion (GFP-dynaminA (Wienke at al.…”
Section: A Model For the Endocytic Pathway In D Discoideummentioning
confidence: 99%
“…Concerning the biosynthetic pathway, lysosomal enzymes are synthesized as precursor polypeptides (Mierendorf et al, 1985;Wood and Kaplan, 1985;Cardelli, 1986;Bush and Cardelli, 1989), and short N-terminal "fpro" regions, proteolytic processing, and the clathrin heavy chain are important in regulating targeting of hydrolases (Richardson et al, 1988;Ruscetti et al 1994;Ruscetti and Cardelli, unpublished results). N-linked mannose-rich oligosaccharide side chains and sulfate and probably phosphate sugar modifications only influence the rate of transport of the enzymes to lysosomes and not the fidelity of the targeting process Freeze et al, 1990).…”
Section: Introductionmentioning
confidence: 99%